Exploring potential of grape in Malwa region - Kanwar, Jyoti; Naruka, I S; Saniya, Saniya; Singh, P P; Anjanawe, S R (Indian Horticulture, 2019)
The country is in the midst of a horticulture revolution. Viticulture in India started in early 1960 and today assumes an important position in horticulture crop in view of its area occupied, production, value addition and job creation in both rural and urban areas. Grape is emerging as an important fruit crop under Malwa region of central India. Globally, grape cultivation is concentrated in temperate region, while our grape cultivation is confined to tropical and peninsular belt and now started diversification to other parts with some promising cultivars. Our prime objective would be harnessing viticulture and enology science to ensure comprehensive and sustained grape production through crop improvement, assessment, refinement and adoption of most appropriate and precisive technologies in grape production and value addition thereby increasing net returns to grape growers and all the stakeholders involved in the industry.